Benoten und Beurteilen im künstlerisch-gestalterischen Unterricht der Sekundarstufe Herausforderungen und Spielräume für (in Ausbildung befindliche) Lehrer:innen - Kollars, Luise (Per EduArt. Kunstpädagogische Materialien für Studium und Schule, 2023)
In the artistic and creative subjects of art and design as well as technology and design, questions of assessment and grading raise specific dilemmas or polylemmas in education as well as in teaching practice. This article opens up the problem context around assessment and marking, explores both subject specifics and legal foundations and thus develops, among other things, a disciplinary-historical approach to challenges as well as leeway for secondary school teachers (in training).